Perancangan Jalur FTTH (Fiber to the Home) di Desa Kota Pari Menggunakan Applikasi SmallWord - Fachrid Wadly; Wirda Fitriani; Muslim (STMIK Budi Darma, 2023)
The rapid development of technology has increased people's need for communication networks, especially fast internet, so media access with high bandwidth is needed to meet these needs. Network technology using copper media currently has limited bandwidth to meet the needs of internet subscribers, especially Telkom subscribers. Therefore, the copper access network is modernized with a fiber optic network. One of them is planning the construction of a fiber-to-the-home (FTTH) network. The design of the Fiber To Home network will be implemented in the village of Kota Pari, a village in the Pantai Cermin sub-district, Serdang Bedagai, North Sumatra. The design of this distribution network uses Google Earth while the method used in this design uses the SmallWorld application. Researchers plan to build a fiber-to-the-home (FTTH) network using Smallworld. In this final design study, the FTTH design process begins with the design of feeder cables and distribution cables to customers' homes with installation distances that have power according to ITU-T G.984 standards and regulations from PT. Telkom, namely the distance does not exceed 20 km and the receiving power is -28 dBm. The design or planning for the construction of the FTTH network by implementing the Smallworld application is still within standardization limits, so this design is feasible to implement.